Community-Based Nutrition Education to Prevent Stunting: Integrating the One Day One Egg Program and Love Language Parenting - Novianti Rizki Amalia; Eneng Daryanti; Asep Mulyana; Rikky Gita Hilmawan; Deni Wahyudi; Euis Teti; Fitriani Mardiana; Novi Nur Ratnasari; Anida Izatul Islami (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Stunting remains a public health problem that requires comprehensive intervention, particularly through nutritional fulfillment and strengthening parenting patterns. Parents are often expected to provide adequate nutrition for their toddlers without understanding the proper parenting patterns. This community service activity aims to increase mothers' knowledge of toddlers regarding protein fulfillment through the One Day One Egg program, using the love language approach, as a stunting prevention effort. The method used was health education through interactive seminars, discussions, and educational media in the form of presentations and booklets. The activity was carried out with 45 mothers with toddlers aged 3–5 years in the Cikiara area. Evaluation was conducted using a questionnaire-based pre-test and post-test to measure changes in participants' knowledge. The results showed a significant increase in knowledge after the intervention. Participants' understanding of the One Day One Egg concept and egg processing methods increased from 31.01% to 94.03%. Understanding of the application of love language-based parenting increased from 10.15% to 80.79%. All participants also showed high enthusiasm during the activity and were able to explain the benefits of eggs, proper processing techniques, and the five types of love languages in feeding children. This program demonstrates that integrating nutrition education with appropriate parenting approaches can improve parents' knowledge and preparedness to meet toddlers' nutritional needs. Ongoing collaboration between health workers, cadres, and the community is necessary to support longer monitoring periods and the need for anthropometric measurements.